Memperkokoh Posisi Departemen Kesehatan dalam Sektor Kesehatan Publik - Hasanbasri, Mubasysyir (JKAP (Jurnal Kebijakan dan Administrasi Publik), 1999)
There have been many dissappointed tendencies that health services are currently biased to the more wealthy groups in the society. Corporatisms, competitions, and the emanation of more profit-oriented health institutions have put aside the public health service for the poor. Unfortunately, even the Department of Health have failed to stand for its fundamental functions in maintaining the public health and protecting the unfortunate people. The Department have been unable to respond the competitive environment and prevent the brain drain of qualified doctors from the public hospitals to the private institutions. It is suggested that the Department of Health should reorient its mission and tasks by applying strategic management approach. This new approach should also be accompanied with stronger external control of the public through the parliament and other pressure group; in the society. The author points out the importance of two elements of the society which would be effective as the control: 1) the researchers, who should be more assertive in contending the inequality of public health services; and 2) the NGO activists, who should be more sensitive and susceptible to various issues in public health. Finally, it is very important that the Department of Health has to comply with the public accountability so that their programmes would be more focused on objective issues of public health.